Transforming Molecular Geometry Learning through EddPuzzle Interactive Videos to Improve High School Students' Visual Intelligence - Revani Putri Iswaji; Kusumawati Dwiningsih (STAI Hubbulwathan Duri, 2025)
Understanding molecular geometry poses a significant challenge for high school students due to its abstract nature, often leading to misconceptions. This study aims to develop and evaluate an EddPuzzle-based interactive video to enhance students’ conceptual understanding and visual intelligence in molecular geometry. Employing a Research and Development (RD) method, the study adopts the 4D model (Define, Design, Develop, Disseminate) but is limited to the development phase. The interactive video was validated by three experts and achieved a median score of 4 across content, construct, and visual intelligence criteria, indicating excellent validity. The product was tested on 30 eleventh-grade students using a one-group pretest-posttest design. The results showed a significant improvement in students’ understanding and visual intelligence, supported by N-Gain scores—93.3% of students reached the high category for cognitive tests, and 86.7% for visual intelligence tests. The Wilcoxon Signed-Rank Test confirmed a statistically significant difference (p 0.05) between pretest and posttest scores. Student feedback indicated high practicality: 100% expressed interest in using the media, 97.8% found the material easier to understand, and 96.7% considered the video user-friendly. These findings suggest that EddPuzzle-based interactive videos are effective and feasible tools for improving students’ visual intelligence in chemistry learning. Integrating interactive technology into science education supports more engaging and student-centered learning aligned with 21st-century education goals.